Microbiological Applications : Laboratory Manual in General Microbiology - Benson, Harold J. (McGraw-Hill, 2002)
Meant for undergraduate microbiology laboratory courses. This manual contains illustrated exercises and four-color format. It is aimed at either a majors or non-majors lab course.